High-performance lithium storage of Ti3+-doped anatase TiO2@C composite spheres. Issue 102 (19th October 2016) - Chen, Xiaoying; Liu, Li; Yi, Lingguang; Guo, Guoxiong; Li, Min; Xie, Jianjun; Ouyang, Yan; Wang, Xianyou
Abstract : Ti 3+ -Doped anatase TiO2 @C composite spheres as the anode materials for lithium ion batteries. Abstract : Ti 3+ -Doped anatase TiO2 @C composite spheres (TD-TiO2 @C) are synthesized for the first time by the solvothermal method, followed by calcination using as-prepared anatase/TiO2 -B hybrid TiO2 spheres and glycerol solution in alcohol as reactants. TD-TiO2 @C spheres exhibit excellent electrochemical performance as anode materials for lithium ion batteries (LIBs). The electrodes not only exhibit a superior capacity of 244.80 mA h g −1 at 1C (0.168 A g −1 ) after 100 cycles, but also show an eminent rate capability. TD-TiO2 @C spheres retain discharge capacities of 171.78, 143.45, 119.17, 105.82 mA h g −1 after 500 cycles at 5C, 10C, 20C, 30C, holding a capacity retention as high as 91.0%, 84.2%, 82.1%, 82.0% when compared with discharge capacities at the 10th cycle, respectively. The improved electrochemical properties are mainly due to the synergistic effects of carbon coating and Ti 3+ doping, which can enhance significantly the inherent electronic conductivity of TiO2 . Therefore, TD-TiO2 @C can be an attractive candidate for anode materials in LIBs, also with great promise.